The protective effects of bone morphogenetic protein-7 against epithelial injury and matrix metalloproteases upregulation induced by silica in vitro. (September 2017) - Liang, D; An, G; Zhu, Z; Wang, Y; Yang, G; Li, X; Niu, P; Chen, L; Tian, L
Objective: We investigate the effects of bone morphogenetic protein-7 (BMP-7) on models with silica-induced and macrophage-mediated fibrosis and its possible mechanisms in vitro. Methods: Rat alveolar II epithelial (RLE-6TN) cells were incubated with the supernatant of mouse macrophage-like cells (RAW264.7) and treated with 0, 25, 50, and 100 μg/mL silica. Using Western blotting, the epithelial markers (surfactant proteins-C and E-cadherin) and the mesenchymal markers (fibronectin (FN) and viminten (Vim)) were detected. After neutralizing the BMP-7, the progress of fibrosis was assessed by the content of hydroxyproline (Hyp) and collagen I, III protein levels as well as the Smad signaling pathway proteins, including phosphorylated Smad1/5(P-Smad1/5) and phosphorylated Smad2/3(P-Smad2/3). Collagen I was also identified by immunofluorescence and pretreated with SB-431542, LDN-193189, or anti-BMP-7-neutralizing antibody. In addition, the levels of matrix metalloproteinase-2 (MMP-2) and MMP-9 were detected using Western blotting. Results: The model of RLE-6TN cells was established successfully, the expressions of Vim, FN, MMP-2, and MMP-9 were upregulated, while the concentration of silica is increased. Neutralizing BMP-7 stimulated the decrease of P-Smad1/5 and the increase of P-Smad2/3, as well as the collagen I, collagen III, FN, and Hyp via Smad signaling pathway. Furthermore, pretreated with LDN-193189 or anti-BMP-7-neutralizing antibody, the expression of collagen I was increased, yet it was decreased with SB-431542 intervention. Conclusion: The activated BMP/Smad and suppressed transforming growth factor-β/Smad pathways could suppress silica-induced fibrosis via a MMP-dependent mechanism. BMP-7 is expected to be the optimized strategy of delaying the interstitial changes.